Cooling of Individuals: A Design Exploration on Cooling Wearables, to Fight the Heat - Steiner,Nicole (2025)
This study investigates the potential of personal cooling solutions to mitigate heat stress in outdoor sporting environments. As global temperatures continue to rise, heat stress has become an increasing concern, particularly in urban environments where outdoor sport can cause significant thermal discomfort. A mixed methods approach was used, including online research, an experimental cooling study and an expert interview with a climate specialist. Based on these findings, a cooling garment incorporating electric cooling units was designed and tested. The results indicate that spot cooling is an effective and energy efficient way to improve thermal comfort. By targeting specific areas of the body, spot cooling provides significant relief without the high energy requirements of whole-body cooling systems. These findings suggest that integrating spot cooling technology into sportswear could provide a practical and sustainable approach to heat mitigation in outdoor sports. Future research should investigate the long-term usability and wider applications of such cooling garments.
Keywords: body cooling; spot cooling; outdoor sports; thermal comfort; climate adaptation